Digital media marketing and the consumption of sugar-sweetened beverages in Africa: A reception analysis of the multi-channel marketing of Coca-Cola among young Africans from the University of Lagos, Nigeria and Rhodes University, South Africa - Akingbade, Olutobi Elijah (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
This study investigates and examines how Coca-Cola's marketing communications, especially the newer forms of digital, social and mobile media marketing messages/campaigns, are received, understood and made sense of by two sets of purposefully selected young urban African students in Nigeria and South Africa. Embedded within a qualitative research design and underpinned by an interpretative phenomenological analysis (IPA) approach, this study was conducted against the backdrop of the recent surge in the consumption of Sugar Sweetened Beverages (SSBs) which has been directly implicated in the rise of obesity and a variety of non-communicable diseases (NCDs) in Africa. The thesis explores the role of multinational SSBs in this surge, as African countries have become key focus areas for multinational food and beverage companies seeking growth and profits, as home markets decline partly due to better health communications and, in some cases, the implementation of so-called 'sugar taxes' and the attendant negative publicity around these taxes. The focus on young Africans from Nigeria and South Africa was motivated by the similar rapid urbanisations in both countries, often accompanied by changes in diet and greater consumption of fast foods and SSBS, and by South Africa's ranking as the country with the highest prevalence of overweight persons and obesity in Sub-Saharan Africa. Similar rises in national average weights are now also starting to be seen in Nigeria, as are surges of diet-related disease incidence and prevalence. The study is informed by Consumer Culture Theory (CCT) but also draws on other theories and some key concepts from marketing studies, health science and psychology. Methodologically, the study draws on in-person observations, focus group interviews and semi-structured individual in-depth interviews, to explore how Coca-Cola has created a deep and evocative historical 'brandscape' and how it has become a multicultural resource in both South Africa and Nigeria. Through an investigation into the lived experiences of study participants with regards to both their earliest and more recent engagements with Coca-Cola, as a brand and as a product, the study delineates the influence of older generations of Coke enthusiasts and consumers within participants' households and newer spaces of interaction with Coke via interactive, highly personalised social media-centric campaigns. This study explores how the ubiquitous nature of Coca-Cola's aesthetics and signage are engaged with "“ often in very 'sub-conscious' ways "“ by these students and how more recent social media campaigns evoke this multigenerational history. Unpacking study participants' self-understandings of Coke and their often 'sub-conscious' engagements with the SSB, this study explicates the underpinning ideological grounding and how this is sustained over time to become an hegemonic code that does not only confine participants' engagements with SSBs to Coke but also confines their reception of, and engagements with, Coke's media marketing messages/campaigns to those that resonate with the multigenerational history evoked by the SSB. It is within this contextual background that this study brings to the fore participants 'cognitive dissonance' and scepticism and often rank disbelief of the health risks posed by their high levels of Coke consumption. The study concludes that attempts to raise awareness about the dangers inherent in excessive consumption of SSBs in Africa need to be reviewed and rethought. There is a need for long-term, consistent and much more proactive health journalism, alongside public health campaigns in both official and indigenous languages, to dispel the powerful myths created by SSB marketing and explain how SSBs are implicated in the rise of diet-related NCDs in Nigeria and South Africa.
Keywords: Carbonated beverages -- Health aspects -- South Africa; Carbonated beverages -- Marketing -- South Africa; Soft drinks -- Health aspects -- South Africa; Soft drinks -- Marketing -- South Africa; Carbonated beverages -- Health aspects -- Nigeria; Carbonated beverages -- Marketing -- Nigeria; Digital media -- Marketing -- Africa; Soft drinks -- Health aspects -- Nigeria; Soft drinks -- Marketing -- Nigeria; Digital media -- Marketing -- Nigeria; Obesity -- Africa; Nutritionally induced diseases -- Africa; Coca-Cola Company -- Marketing; Rhodes University -- Students -- Attitudes; University of Lagos -- Students -- Attitudes